Revising the Set of 20 Key-Indicators for Sports and Physical Activity in The Netherlands (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The Netherlands has a unique system for monitoring sports and physical activity through a structured set of Key-Indicators, developed in 2014. These indicators provide critical data for evaluating national trends and informing policy decisions. Given the sector’s significant growth, rising societal attention for physical activity, and advances in research, the set of current Key-Indicators is evaluated to determine their relevance, identify necessary revisions, and develop new metrics to address emerging subjects.Project Description: The Key-Indicators are maintained by a collaborative network comprising Statistics Netherlands, VeiligheidNL, NOC*NSF, Mulier Institute, Knowledge Centre for Sport & Physical Activity, and RIVM. The up-to-date numbers of all Key-Indicators are disseminated on www.sportenbewegenincijfers.nl/kernindicatoren, managed by RIVM. In consultation with these partners and the Ministry of Health, Welfare and Sport, criteria were established for the revised Key-Indicators. Key-Indicators should align with the interest of national sport and physical activity policies, be interpretable as single metrics, enjoy expert consensus, offer national (and, where feasible, regional) relevance, and be updated at a minimum frequency of once every four years.The suitability of existing Key-Indicators and opportunities for new subjects were assessed across 12 established themes of the national sport and physical activity data-infrastructure. For each theme, the adequacy of the current Key-Indicators was evaluated alongside data quality and methodological robustness. Experts from both research and policy contributed to the thematic discussions. When necessary, additional research experts were consulted.The revised set includes 25 Key-Indicators, replacing the original set of 20. Among the current Key-Indicators, 18 were retained. One (‘Sports participation 12x per year’) was removed, and two related to physical education were combined into a single metric with separate data per school level. Seven new Key-Indicators were introduced, covering subjects such as physical inactivity, inclusion, diversity, motor skills in children, and governance in sports. Eighteen Key-Indicators are ready for implementation; three require minor refinements, and four need further methodological development.Conclusion: The updated Key-Indicators form a comprehensive monitoring framework, enabling policymakers to adapt sport and physical activity policies based on emerging trends. The Network will oversee ongoing development of new Key-Indicators and ensure consistency and quality over time.